Cocaine/heroin induced rhabdomyolysis and ventricular fibrillation. Issue 3 (1st May 2002) - McCann, B; Hunter, R; McCann, J
Abstract : A case of cardiorespiratory arrest in a 28 year old man after cocaine and heroin ingestion is described. The arrest is attributed primarily to hyperkalaemia/rhabdomyolysis—a recognised consequence of each of these drugs. The administration of naloxone may have been contributory. He developed acute renal failure, disseminated intravascular coagulopathy with consequent lower limb compartment syndrome requiring fasciotomy. Ventricular fibrillation was identified at thoracotomy.